2013
DOI: 10.1097/jto.0b013e31829f6a5f
|View full text |Cite
|
Sign up to set email alerts
|

WT1 Promotes Invasion of NSCLC via Suppression of CDH1

Abstract: WT1 expression was correlated with clinical stage, metastasis, and survival rate in 159 NSCLC patients. Via direct binding to the promoter, WT1 could suppress CDH1 and promote NSCLC invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
2
32
0
1
Order By: Relevance
“…Furthermore, overexpression of WT1 enhanced proliferation through upregulation of cyclin D1 and p-pRb in NSCLC cells [12]. WT1 suppressed the expression of E-cadherin through directly binding its promoter to enhance the invasion [15]. Thus, WT1 plays an important role in promoting proliferation and invasion in NSCLC cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, overexpression of WT1 enhanced proliferation through upregulation of cyclin D1 and p-pRb in NSCLC cells [12]. WT1 suppressed the expression of E-cadherin through directly binding its promoter to enhance the invasion [15]. Thus, WT1 plays an important role in promoting proliferation and invasion in NSCLC cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether miR-193a can regulate E-cadherin expression is not determined. Because WT1 is implicated in the metastasis of NSCLC through inhibiting the expression of E-cadherin [15], we hypothesized that one mechanism of anti-metastasis activity of miR-193a might perform by modulating WT1-E-cadherin axis.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they concluded that low WT1 expression predicted poor prognosis in patients with NSCLC. On the other hand, two recently published papers from the same group determined that WT1 promotes the invasion of NSCLC via the suppression of E-cadherin, and it increases cell proliferation in NSCLC cell lines through upregulation of cyclin D1 and pRb [43], [44]. Therefore, the exact role of WT1 in NSCLC is a current matter of debate, and more prospective studies are required to confirm its importance.…”
Section: Discussionmentioning
confidence: 99%
“…By in vitro experiments, we showed that WT1 can promote NSCLC invasion through direct binding to the CDH1 promoter [19]. Furthermore, WT1 was found to promote NSCLC cell proliferation by upregulating Cyclin Dl and p-pRb expression in vitro and in vivo [20] .…”
Section: Introductionmentioning
confidence: 99%